Keefektifan Model Project Based Earning Berbantu Power Point terhadap Hasil Belajar IPA SDN 05 Palembang - Sri Astuti; Nora Surmilasari; Lukman Hakim (Journal on Education, 2023)
The purpose of this study was to determine the effectiveness of the Power Point-assisted Project Based Learning model on science learning outcomes at SDN 05 Palembang. The method used is the Quasi Experimental Design method using the Nonequivalent Control Group Pretest-posttest design. The population in this study amounted to 50 students consisting of 5A and 5B, the sample used was taken in class 5A as many as 25 students. The data collection technique is done by testing and documentation. The analysis technique used is the t test (Independent Samples T-test). The average pretest score for the experimental class was 59.8, while the control class' pretest average was 46.6. The average posttest score for the experimental class was 87, and the posttest average for the control class was 63.4. The results of the hypothesis show that sig 2 (tailed) gets a value of 0.00 <from a significant level of 5% or 0.05 so that Ha is accepted and H0 is rejected. There is an influence of the Power Point-assisted Project Based Learning model on science learning outcomes at SDN 05 Palembang.